2013
DOI: 10.2478/s13380-013-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological rehabilitation for bipolar disorder — A single case design

Abstract: BackgroundCognitive impairments are common ndings in neuropsychiatric diseases and contribute to restrictions in work and social skills [1,2].Cognitive functioning has been shown to be a predictor of a positive prognosis in psychiatric intervention [1,3].Meta-analytic studies [4,5] [6]. Given that cognitive deficits are predictive of a lower quality of life [7], it is logical that they are a potential treatment target for neuropsychological rehabilitationNR is an active process of capacity building for people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Studies like this can provide mental health practitioners with useful intervention strategies, because investigators soon found that effectiveness of psychosocial interventions in these patients is bound to considering their cognitive limitations ( 24 ). As a new approach in last few years, it aims to help these patients by intervening on their basic cognitive components, called neuropsychological remediation or cognitive rehabilitation ( 25 ). By manipulation of basic cognitive processes, these interventions are supposed to improve cognitive functions and consequently promote psychosocial functioning of bipolar patients ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies like this can provide mental health practitioners with useful intervention strategies, because investigators soon found that effectiveness of psychosocial interventions in these patients is bound to considering their cognitive limitations ( 24 ). As a new approach in last few years, it aims to help these patients by intervening on their basic cognitive components, called neuropsychological remediation or cognitive rehabilitation ( 25 ). By manipulation of basic cognitive processes, these interventions are supposed to improve cognitive functions and consequently promote psychosocial functioning of bipolar patients ( 26 ).…”
Section: Introductionmentioning
confidence: 99%